APPLICATION OF HADITH AS A SOURCE OF LAW IN DETERMINING THE FATWA OF THE INDONESIAN COUNCIL OF ULAMA (MUI) - Farida, Umma; Kasdi, Abdurrohman (RIWAYAH, 2023)
Indonesian Muslims tend to seek religious solutions to face their problems, one of which is by referring to the fatwa of the Indonesian Ulama Council (MUI). Considering the position of hadith as a source of teachings in Islam, exploring the existence of hadith in legal formulations and the establishment of fatwas is also important. This research aims to reveal the use and absorption of hadith as a source of Islamic law in the determination of the Fatwa of the Indonesian Ulama Council as stated in the MUI Fatwa Association Book since 1975, totalling 173 fatwas, focusing on socio-cultural fatwas of 64 fatwas. This research used a qualitative method with a descriptive-critical approach. The research results show that of the 64 fatwas in the social and cultural fields, almost the majority use hadith as a source of law in formulating their fatwas. There are 51 fatwas related to social and cultural fields that use hadith as a source of law, while 13 other fatwas do not involve hadith in their legal sources. The total number of hadiths that are a source of law in the formulation of MUI fatwas in the socio-cultural field is 222 hadiths. Quoting hadiths in the determination of the fatwa of the Indonesian Ulama Council (MUI) in the Social and Cultural Sector as stated in the MUI Fatwa Association since 1975 generally uses two techniques: First, citing by including the source or narrator who transmitted the hadith from the Prophet PBUH. Second, quoting without mentioning the name of the hadith transmitter. All the hadith referred to by the MUI are of authentic quality and can be verified for their authenticity. [Muslim Indonesia memiliki kecenderungan untuk mencari solusi yang bersifat religius dalam menghadapi problem mereka, salah satunya dengan merujuk pada fatwa Majelis Ulama Indonesia (MUI). Mengingat kedudukan hadis sebagai salah satu sumber ajaran dalam Islam, maka menggali eksistensi hadis dalam formulasi hukum dan penetapan fatwa juga menjadi penting. Penelitian ini bermaksud mengungkap penggunaan dan penyerapan hadis sebagai salah satu sumber hukum Islam dalam penetapan Fatwa Majelis Ulama Indonesia sebagaimana yang tertuang dalam Buku Himpunan Fatwa MUI sejak 1975 yang berjumlah 173 fatwa dengan memfokuskan pada fatwa bidang sosial budaya sebanyak 64 fatwa. Penelitian ini menempuh metode kualitatif dengan pendekatan deskriptif-kritis. Hasil penelitian menunjukkan bahwa dari Dari 64 fatwa bidang sosial dan budaya hampir mayoritas menggunakan hadis sebagai sumber hukum dalam perumusan fatwanya. Terhitung 51 fatwa terkait bidang sosial dan budaya yang menggunakan hadis sebagai salah satu sumber hukum, sedangkan 13 fatwa lainnya tidak melibatkan hadis dalam pengambilan sumber hukumnya. Jumlah keseluruhan hadis yang menjadi sumber hukum dalam perumusan fatwa MUI dalam bidang sosial budaya adalah 222 hadis. Pengutipan hadis dalam penetapan fatwa Majelis Ulama Indonesia (MUI) Bidang Sosial dan Budaya sebagaimana yang tertuang dalam Himpunan Fatwa MUI sejak 1975 secara umum menempuh dua teknik: Pertama, pengutipan dengan menyertakan sumber atau periwayat yang mentransmisikan hadis tersebut dari Nabi Saw. Kedua, pengutipan tanpa menyebutkan nama transmittor hadis. Keseluruhan hadis yang dirujuk MUI tersebut berkualitas shahih dan dapat dipertanggung jawabkan kehujjahannya.]